“We Don't Know anything about Whales:” Ecological Knowledge and Ways of Knowing in Ulukhaktok, NT, Canada - Collings, Peter; Pearce, Tristan; Kann, Joseph (NRC Research Press (a division of Canadian Science Publishing), 2017)
This paper reports on interviews conducted during June and July, 2015, to document ecological knowledge of beluga whales in Ulukhaktok, NT. Beluga whales are not a traditionally available or important species for Ulukhaktomiut, but they have appeared in increasing numbers in the waters around the community, and hunters have actively pursed and taken them. We conducted interviews in English with 31 Inuit about their beluga knowledge. A Key Words in Context (KWIC) analysis of the word “know” in the narratives reveals different conceptions of what it means to know something about whales. “Know” variously references practical skill, concern and empathy for others, or the developing awareness of one’s place in the world. Each of these meanings is coded uniquely in Inuinnaqtun, providing insights about the important differences between researchers and Inuit in how “ecological knowledge” is understood and activated. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.